SGK1 (glucose transport), dishevelled2 (wnt signaling), LC3/p62 (autophagy) and p53 (apoptosis) proteins are unaltered in Lafora disease (The All Results Journal, 2016)
Glycogen forms through the concerted actions of glycogen synthase (GS) which elongates glycogen strands, and glycogen branching enzyme (GBE).  Lafora disease (LD) is a fatal neurodegenerative epilepsy that results from neuronal accumulation of hyperphosphorylated glycogen with excessively long strands (called polyglucosans).  There is no GBE deficiency in LD.  Instead, the disease is caused by loss-of-function mutations in the EPM2A or EPM2B genes, encoding, respectively, a phosphatase, laforin, and an E3 ubiquiting ligase, malin.   A number of experimentally derived hypotheses have been published to explain LD, including:  The SGK1 hypothesis - Phosphorylated SGK1 (pSGK1) raises cellular glucose uptake and levels, which would activate GS.  Based on observing increased pSGK1 in LD mice it was proposed that raised pSGK1 leads to polyglucosan generation through GS hyperactivation.  The Dishevelled2 hypothesis - Downregulating malin in cell culture was reported to increase levels of dishevelled2, which through the wnt/glycogen synthase kinase-3 pathway would likewise overactivate GS.  The Autophagic defect hypothesis - Polyglucosans may be natural byproducts of normal glycogen metabolism.  LD mice were reported to be autophagy-defective.  LD would arise from failed autophagy leading to failed polyglucosan clearance.  Finally, the p53 hypothesis - laforin and malin were reported to downregulate p53, their absence leading to increased p53, which would activate apoptosis, leading to the neurodegeneration of LD.  In the present work we repeat key experiments that underlie these four hypotheses.  We are unable to confirm increased pSGK1, dishevelled2, or p53 in LD mice, nor the reported autophagic defects.  Our work does not support the above hypotheses in understanding this unique and severe form of epilepsy.